2014
DOI: 10.1097/aog.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Survival After Prolonged Preterm Premature Rupture of Membranes Before 24 Weeks of Gestation

Abstract: With antenatal steroid exposure and aggressive pulmonary management, survival to discharge after prolonged preterm PROM was 90%. Pulmonary morbidities were common. Of note, the data were limited to women who remained pregnant 1 week or longer after rupture of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…Although the role of amniotic fluid as a predictor of mortality has recently been questioned [9,18], our data, including a larger number of women, and in line with previous reports [1,4,12,30,31], suggest that the presence of a lower LVP at admission is associated with a significantly higher rate of perinatal mortality.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Although the role of amniotic fluid as a predictor of mortality has recently been questioned [9,18], our data, including a larger number of women, and in line with previous reports [1,4,12,30,31], suggest that the presence of a lower LVP at admission is associated with a significantly higher rate of perinatal mortality.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Hadi et al [19] evaluated the role of the mean of amniotic fluid volume throughout pregnancy showing a higher neonatal survival to discharge in women with an adequate amniotic fluid volume until delivery. However, Brumbaugh et al [9] recently observed that neonatal survival to discharge in prolonged EPPROM was not related to the evolution of the LVP along time. They defined prolonged EPPROM as latency to delivery of ≥7 days.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some recent studies, survival rates can be as high as 70 to 90%. (1,(5)(6)(7) In addition to the increased risk of mortality, these neonates are also at risk of several morbidities including hypoxemic respiratory failure, sepsis, limb contractures, potential neonatal asphyxia due to cord compression or placental abruption in addition to the risks of (extreme) prematurity. Hypoxemic respiratory failure is attributable to pulmonary hypoplasia and arterial pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%